Implementasi Shalat Berjamaah Dalam Pembentukan Akhlak Siswa - Thio Apri Yanda; Al Ikhlas (An-Nuha, 2022)
This study aims to determine the implementation of congregational prayer and the morals that students appear after praying together. This research uses a qualitative research method with a descriptive research type. Researchers used data collection methods, namely observation, interviews, and documentation. source of data taken through purposive sampling technique with informants namely principals, teachers, and students. data analysis techniques using data reduction, data presentation, and drawing conclusions. In this study, it was found that first, the principal had facilitated and supervised the implementation of congregational prayers in schools. Second, PAI teachers have taught theory and practice regarding the implementation of congregational prayers and supervised their implementation. Third, for understanding the congregational prayer material, there are some who already understand and some who do not.